Economic Analysis of Inequality in Preventive Health Check-Ups Uptake in Saudi Arabia - Al-Hanawi, Mohammed Khaled; Chirwa, Gowokani Chijere (Frontiers in Public Health, 2021)
Background: Undertaking preventive health check-ups has proven to be an important strategy in the fight against several diseases. However, various socioeconomic circumstances may hinder participating in such an important health exercise for many people. With the growth in the burden of non-communicable diseases in Saudi Arabia, it is thus essential that people take an active role in undertaking preventive health check-ups. However, the extent to which this behavior is determined by inequalities in socioeconomic circumstances remains not well-documented. The aim of this study was to examine the socioeconomic inequalities in undertaking preventive health check-ups in Saudi Arabia, using a national survey with a sample of 11,528 respondents. Methods: Data from the Saudi Family Health Survey conducted in 2018 by the General Authority for Statistics were used for the analysis of this study. Univariate, bivariate, and multivariate logistic regression analyses were employed to examine the socioeconomic factors associated with undertaking preventive health check-ups. Concentration indices were calculated, and associated concentration curves were used to assess the socioeconomic inequalities in preventive health check-ups uptake. Moreover, decomposition analysis was performed to examine the extent to which the socioeconomic variables affect uptake of preventive health check-ups. Results: The results reveal that being older adults, more educated, insured, and married increase the probability of undertaking preventive health check-ups. Regarding socioeconomic inequalities, preventive health check-ups uptake was concentrated among the wealthier (concentration index: 0.0831; P < 0.001). However, some differences were observed in terms of socioeconomic inequality across the regions. Decomposition of the Erreygers index supported the analysis of the determinants and suggested that income, and education were the primary drivers of the associated inequality. Conclusions: These results suggest that the government of Saudi Arabia should develop intervention programs and strategies that promote the uptake of health check-ups among the vulnerable group to reduce inequalities. Of particular importance is the need for more health-related education among the poor and those with lower education in order to raise their awareness on the benefits and advantages of conducting health examinations.